On the social types in Raízes do Brasil - Goldfeder, André; Waizbort, Leopoldo (Revista do Instituto de Estudos Brasileiros, 2009)
The article discusses the employment of social types or human types by Sérgio Buarque de Holanda in his book Raízes do Brasil, first published in 1936, aiming to clarify their position within the realm of the argument construction. It intends to suggest ways of establishing connections between these types and those created by Georg Simmel and Werner Sombart, regarding to their use and construction.